PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP PENGUASAAN KONSEP IPAS KELAS 5 SDN 17 MATARAM - Elwanda, Adya Putri; Muhammad Sobri; Ilham Handika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Project Based Learning model on the mastery of IPAS concepts among fifth grade students at SDN 17 Mataram.This study is classified as quantitative experimental research (pre experimental).The study population consisted of all 16 fifth-grade elementary school students taking the IPAS (Natural and Social Sciences) subject. Sampling in this study employed the one-group pretest posttest design technique.The sample for this study consisted of all fifth grade students at SDN 17 Mataram, divided into an experimental class and a control class.Data collection was conducted using tests, observation, and documentation.The data analysis technique employed in this study utilizes descriptive statistical analysis including a normality test (One Sample Kolmogorov Smirnov Test) inferential statistical analysis (Paired Sample t-test for hypothesis testing), and N-gain score analysis.Based on the results of the paired-sample t-test analysis, a difference was found between the pre-test and post-test learning outcomes regarding the mastery of Science and Social Studies (IPAS) concepts among Grade 5 students at SDN 17 Mataram using the Project-Based Learning model.This is evidenced by the Sig. (2-tailed) value of 0.001 < 0.05.This indicates a significant effect of the project-based learning model on the mastery of IPAS concepts among fifth grade elementary school students, based on the pretest and posttest data.